2004
DOI: 10.3168/jds.s0022-0302(04)70044-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Silymarin, a Natural Hepatoprotector, in Periparturient Dairy Cows

Abstract: Silymarin, a natural acknowledged hepatoprotector used in humans to treat liver diseases, has been tested in dairy cows during peripartum, a period during which animals are subject to subclinical fatty liver. Ten grams of silymarin (76% pure extract consisting in flavonolignans, taxifolin, and other trace compounds) per day, was administered as a water suspension by an oral drench to 15 cows from d 10 before expected calving to 15 d after calving. Milk production was measured, and colostrum, milk, and blood sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
76
0
5

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(93 citation statements)
references
References 29 publications
8
76
0
5
Order By: Relevance
“…No effect of silymarin on the milk composition was observed in our study (data not presented). This is in agreement with findings of Tedesco et al (2002Tedesco et al ( , 2003Tedesco et al ( , 2004b. Changes in plasma parameters after silymarin supplementation were inconsistent.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…No effect of silymarin on the milk composition was observed in our study (data not presented). This is in agreement with findings of Tedesco et al (2002Tedesco et al ( , 2003Tedesco et al ( , 2004b. Changes in plasma parameters after silymarin supplementation were inconsistent.…”
Section: Discussionsupporting
confidence: 82%
“…Similar findings were reported by Tedesco et al (2003). On the other hand, in their later study Tedesco et al (2004b) reported higher milk yield at the beginning of lactation in cows receiving 10 g of silymarin daily during the periparturient period. Vojtíšek et al (1991) also noted higher milk yield in ketotic cows in early lactation treated with 300 g/day of milk thistle meal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the information regarding the advantages and disadvantages of such practice on the metabolic status of dairy cows is limited. Tedesco et al (2004) have shown the potential use of silimarina; i.e. human liver protector, in dairy cows during the transition period.…”
Section: Introductionmentioning
confidence: 99%
“…Silybin, a flavolignane that represents approximately 60%-70% of silymarin, is an antioxidant isolated from the fruits of milk thistle, silybum marianum Gaertn. Interest in this agent has grown in recent years due to its wide array of beneficial pharmacological effects, including antioxidative, anti-lipid-peroxidative, antifibrotic, anti-inflammatory, immunomodulating and even liver regenerating effects [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%